INVESTIGATE THE POST WAR IMPROVEMENTS OF HYDRAULIC INFRASTRUCTURE IN IRRIGATION SYSTEMS OF KANAGARAYAN ARU RIVER BASIN USING HYDROLOGICAL MODEL - Janithra, S.; Pratheeba, J.; Athapattu, B.C.L.; Sampath, D.S.; Sivakumar, S.S. (University of Jaffna, 2018)
Jaffna, Kilinochchi, Mullaitivu, Vavuniya and Mannar districts are under the Northern Province. Most of the northern region got affected due to the civil war around 30 years. Due to this war water resources development were damaged severely. The major, medium and minor irrigation systems were dilapidated conditions. After the resettlement stack holders are engaged with agriculture activities and several investments were done for the irrigation infrastructure. How ever still stack holders suffering with cultivation issues. Most of the area of the Northern Province has been used for pad dy cultivation. During the dry seasons most of the irrigation schemes in this area became dry. Hence the command area of those irrigation schemes cannot be irrigated successfully for two seasons. As a consequence cultivated crops fail and farmers are affected heavily. Hydrological Modeling is a commonly used tool by water resources planners to simulate the hydrological response in a basin due to the precipitation for the purpose of management of basin water. With the in creasing demand for limited water resources in every basin, careful management of water resources becomes more im portant. The Kanagarayan Aru River Basin in Srilanka supplies water to number of new and ancient irrigation systems and the management of water resources in the Kanagarayan Aru River Basin. total catchment area of this River Basin is 906Sq.Km. Important for optimum utilization of water for these irrigation systems in the project continuous rainfall runoff modeling in pat of the Iranamadu Tank, Chemamadu Tank and Kanagarayan Kulam Tank. Storage Irrigation systems using the hydrological Engineering centre – Hydrologic Modeling System (HEC-HMS) VERSION 3.0.1 to estimate the run off in the Kanagarayan Aru River.
Keywords: Kanagarayan aru river basin; Iranamadu; Kanagarayan kulam; Chemamadu irrigation scheme; HEC-HMS Hydrological Modeling